Using data mining methods for risk assessment and intervention planning in diabetic patients-An exploratory study - Ramanathan, Vanisree; Mhamane, Sharyu; Pawar, Jayesh; PK, Nisha; Kumar, Ujjwal; Tripathi, Shailesh; Pradhan, Keerti B; Bhattacharya, Sudip (Indian Journal of Community Health, 2024)
.